THE BRANDING STRATEGY OF TANJUNGSARI BATOK TOURISM VILLAGE IN BLITAR CITY AS A TOURIST DESTINATION - Bina Andari; Hery Suprayitno (Universitas Islam Balitar, 2020)
The purpose of this study is to determine the implementation of the city branding strategy in Tanjungsari Batok Tourism Village as a tourist destination or not. This research method uses descriptive qualitative analysis method, with a case study approach. Data collection techniques in this study in the form of observation, documentation and interviews. The results of this study are the implementation strategy of the Batok Market in Tanjungsari Kelurahan as City Branding by the Tanjungsari Kelurahan Government which has been going well. Starting from the application of (1) good image marketing through the Batok Market event that carries the traditional theme, (2) marketing of attractions / attractions through the Batok Market event that presents traditional children's games, (3) marketing of infrastructure through the website and reporting on line Kampung Batok activities, and (4) marketing of residents through the formation of Community Groups (Pokmas).